Treatment of kidney transplant recipients with ACEi/ARB and risk of respiratory tract cancer: a collaborative transplant study report - Opelz, Gerhard; Döhler, Bernd (American journal of transplantation, 2011)
Whether treatment with angiotensin-converting enzyme inhibitors (ACEi) and/or angiotensin receptor blockers (ARB) increases the risk of cancer is controversial. Collaborative transplant study data were analyzed according to whether kidney transplant recipients were treated with ACEi/ARB at year 1. Twenty-four thousand and ninety patients were studied of whom 9079 (38%) patients received ACEi/ARB. There were 872 nonskin malignancies during years 2-8 posttransplant, including 107 respiratory/intrathoracic tumors. The standardized incidence ratio (SIR) for all nonskin malignancies was similar between the ACEi/ARB (1.91) and no ACEi/ARB (1.81) groups (p = 0.42). For respiratory/intrathoracic tumors, however, SIR was significantly higher with ACEi/ARB (1.65 vs. 1.09 for no ACEi/ARB, p = 0.033). Multivariate Cox regression analysis showed that ACEi/ARB treatment was not associated with an increased risk of respiratory/intrathoracic tumors in nonsmokers. In patients with a history of smoking, however, the risk of respiratory/intrathoracic tumors was 2.77 (95% CI 1.19-6.43, p = 0.018) in patients without ACEi/ARB treatment as compared to 7.10 (95% CI 3.27-15.4, p < 0.001) in patients treated with ACEi/ARB. Our data indicate that in kidney transplant recipients, ACEi/ARB treatment is associated with a significant increase in the rate of respiratory/intrathoracic tumors in the subpopulation of patients with a history of smoking.